Combination Therapy with Monoamine Oxidase Inhibitors and Other Antidepressants or Stimulants: Strategies for the Management of Treatment‐Resistant Depression. Issue 4 (April 2015) - Thomas, Samantha J.; Shin, Mirae; McInnis, Melvin G.; Bostwick, Jolene R.
<x xml:space="preserve">Abstract</x> Treatment‐resistant depression (TRD) is a major health concern. More than 40% of patients treated for major depressive disorder with an appropriate antidepressant dose for an adequate duration fail to respond. Further, approximately half of adults with major depressive disorder fail to achieve sustained remission despite various medication trials. The utilization of monoamine oxidase inhibitors (MAOIs) for the treatment of depression in clinical practice today is low due to their widely known adverse effects, some of which may be life threatening, and the risk for dietary and drug interactions. For these reasons, MAOIs are not recommended to be prescribed along with other antidepressants or certain prescription or nonprescription drugs. Pharmacologic options are limited for individuals with TRD, however, and there is a paucity of data on the efficacy of MAOIs in combination with other antidepressants for the management of TRD. We performed a search of the PubMed database (inception through January 25, 2015) to identify cases that illustrate the potential utility, as well as risks, of combination treatment with MAOIs and other antidepressants for the management of TRD; 18 articles met the criteria for our search. In addition, we performed a retrospective case series by reviewing the medical records of 29 adults treated for depression with an MAOI plus another psychotropic agent (an antidepressant or stimulant medication) between 2003 and 2012 at a large Midwestern teaching hospital. We compared the findings of the published experience with our local experience to allow for more informed decisions regarding pharmacotherapy in patients with TRD. We separated the local experience into two groups: 15 cases with the selective MAO type B inhibitor selegiline combined with medications presumed to increase the risk of serotonin syndrome and 14 cases with nonselective MAOIs (phenelzine and tranylcypromine) combined with other contraindicated medications. Although risks of combination treatment certainly exist with selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors, or clomipramine, the current literature supports cautious use of combining MAOIs with other antidepressants in patients with TRD who have failed multiple treatment modalities. In addition, the data from the 29 patients receiving combination therapy with an MAOI and another antidepressant or stimulant medication revealed that 21% improved significantly, with no complications. This case series and literature review suggest that when used under close supervision and under the care of an experienced clinician in psychiatry, combination therapy may be a consideration for the management of TRD in patients not responding to monotherapy or other combinations of antidepressants.